The Juridical Implications for Violating the Contents of the Peace Deed Made by the Parties before a Notary in the Conception of Legal Certainty - Diana, Della Ochta; Bawono, Bambang Tri (Jurnal Konstatering, 2023)
The settlement of disputes or cases is largely inseparable from the method of settlement through trials in court. However, in reality, disputes or cases that have been filed in court often receive complaints from the public, one of which is a very long settlement process. Therefore there are many ways to resolve disputes outside the courtroom, one of which is through mediation by reconciling the two parties by making peace deed. This research was conducted to find out and analyze the contents of the peace deed according to the concept of legal certainty and the legal consequences for those who violate the contents of the deed. The method used by the author in this thesis research is a normative legal research method using the statutory approach as the basic basis for research and analysis based on literature and other scientific works. The results of the discussion of the thesis research based on the formulation of the problem listed by the author explain that the deed of reconciliation made by a notary outside the court still has the force of law and legal certainty as well as the power of a judge's decision which cannot be changed if the deed has been registered in the form of a lawsuit so that if in the future there are violations committed by one of the parties, the power of the deed cannot be denied anymore and has permanent legal force and cannot be appealed or cassation against it. As well as for violations committed by one of the parties. Keywords: Case; Deed; Notary; Peace.